PENGARUH SENAM HAMIL BIRTH BALL DENGAN MUATAN EDUKASI PERSIAPAN PERSALINAN TERHADAP KECEMASAN IBU HAMIL - Wenny Indah Purnama Eka Sari; Kurniyati Kurniyati (Politeknik Kesehatan Kementerian Kesehatan Banten, 2021)
During pregnancy, there is an imbalance of the hormones estrogen and progesterone which causes physical and psychological changes. A common psychological change during pregnancy is anxiety. Pregnant women who experience anxiety during pregnancy will increase the risk not only to the mother but also to the baby. One of the efforts to overcome the anxiety of pregnant women is to do pregnancy exercises use birth ball and education of childbirth preparation. This study aims to analize the effect of pregnancy exercise use birth ball and education of child birth preparation on pregnant women anxiety. This research method use quasi experimental with non randomized pretest-posttest control group design. Subject is divided into two groups, intervention and control with total sample 34 respondens. Anxiety of pregnant women assessment using Zung Self-Rating Anxiety Scale (ZSRAS). Statistical test using Mann Whitney test with p value p=0,000 showed differences between intervention group and control group p<0,05, there is a significant decrease in anxiety scores in the intervention group compared to the control group. Conclusion of this study is pregnancy exercises use birth ball and education of childbirth preparation reduces anxiety in pregnant women.